ANALISIS PENCEMARAN NAMA BAIK GUBERNUR LAMPUNG OLEH TIKTOKER BIMA (Kajian Pasal 28 Ayat 2 Juncto Pasal 45 A ayat 2 UU ITE Tentang Ujaran Kebencian Yang Mengandung Unsur SARA) - Dwi Cahyo, Anggoro; Fitriyantica, Agnes; Hermawan , Muhammad Bayu (CV. Era Digital Nusantara, 2023)
The rise of diverse social media makes it easier for people to communicate and share information with other communities. On the other hand, hate speech that smells of SARA also thrives, it has a dangerous impact when it is carried out through social media because of its wide reach and rapid spread. A legal approach has been taken and the perpetrators of hate speech have been legally processed, but it still does not have a deterrent effect. Hate speech on social media that never subsides occurs for many reasons. First, the lack of digital media literacy programs for the community. The second is the lack of clarity in law enforcement. The third that is no less important is the political conflict at the elite level. Likewise with the case that occurred with Tiktoker Lampung Bima Yudho Saputra, who was considered to have gone too far in criticizing the Lampung provincial government. So he was reported to the police and eventually in criminal proceedings. In its journey the ITE Law became a rubber article to criminalize and silence those who criticized the government. The type of research used in this research is normative legal research. The approach used in this study is the statutory approach (statute approach), conceptual approach (conceptual approach) and case approach (case approach).